2021
DOI: 10.1080/21655979.2021.1896116
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ZNF609 functions as a competing endogenous RNA in regulating E2F transcription factor 6 through competitively binding to microRNA-197-3p to promote the progression of cervical cancer progression

Abstract: Countless studies have demonstrated that Circular RNAs (circRNAs) exert vital effects in regulating tumorigenesis of various cancers. CircRNA ZNF609 (circ-ZNF609) has been reported as an oncogene in various human cancers. Nevertheless, its regulating effect in cervical cancer (CC) remains to be further explored. RT-qPCR was adopted to measure circ-ZNF609, miR-197-3p and E2F6 levels. CC cell proliferation, migration and invasion were analyzed via CCK-8 and transwell assays. Dual-luciferase reporter assay was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Circ_AKT1 accelerates CC progression by up-modulating AKT1 through miR-942-5p [ 21 ]. Circ-ZNF609 can promote the expression of E2F transcription factor 6 through competitively binding with miR-197-3p to facilitate the proliferation, migration and invasion of CC cells [ 22 ]. In this work, we identified that, circ_0000228, derived from ZEB1 transcript, which is transcribed from chromosome chr10:31661946–31676195, was up-regulated in CC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_AKT1 accelerates CC progression by up-modulating AKT1 through miR-942-5p [ 21 ]. Circ-ZNF609 can promote the expression of E2F transcription factor 6 through competitively binding with miR-197-3p to facilitate the proliferation, migration and invasion of CC cells [ 22 ]. In this work, we identified that, circ_0000228, derived from ZEB1 transcript, which is transcribed from chromosome chr10:31661946–31676195, was up-regulated in CC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The previous publications in Bioengineered also affirmed the involvement of circRNA/miRNA/mRNA axis in different tumors. For example, circ-LRP6 functioned as an oncogenic regulator in esophageal squamous cell carcinoma by targeting the miR-182/Myc signaling [ 37 ] and circ-ZNF609 facilitated the development of cervical cancer through the miR-197-3p-mediated E2F6 upregulation [ 38 ]. Also, circ_0000117 promoted cell proliferation and invasion in gastric cancer via regulating STAT3 expression by competitively binding to miR-337-3p [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is globally among the dominant reasons for cancer-related deaths in females [24][25][26][27]. Evidence from clinical and experimental studies has shown that TCS has anti-tumor activity in a variety of anti-cancer treatments, including cervical cancer [16,28,29].…”
Section: Discussionmentioning
confidence: 99%